2005
DOI: 10.1158/1078-0432.ccr-05-0840
|View full text |Cite
|
Sign up to set email alerts
|

Histone Deacetylase Inhibitor FK228 Activates Tumor Suppressor Prdx1 with Apoptosis Induction in Esophageal Cancer Cells

Abstract: Purpose: The histone deacetylase inhibitor FK228 shows strong activity as a potent antitumor drug but its precise mechanism is still obscure. The purpose of this study is to reveal the effect of FK228 on gene expression in the cell and to determine the mechanism of the antitumor activity of FK228 for further clinical applications. Experimental Design and Results: Microarray analysis was applied to verify the gene expression profiles of 4,608 genes after FK228 treatment using human esophageal squamous cell canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
40
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 38 publications
7
40
0
Order By: Relevance
“…Moreover, the Prdx1 knockout mice generated malignancies in the intestine, lymphomas, and sarcomas with a high frequency (6). In addition, we previously reported that FK228, one of the novel HDAC inhibitors, induced growth inhibition and apoptosis in ESCC (7). HDAC plays a fundamental role in regulating gene expression and chromatin assembly (9,10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the Prdx1 knockout mice generated malignancies in the intestine, lymphomas, and sarcomas with a high frequency (6). In addition, we previously reported that FK228, one of the novel HDAC inhibitors, induced growth inhibition and apoptosis in ESCC (7). HDAC plays a fundamental role in regulating gene expression and chromatin assembly (9,10).…”
Section: Discussionmentioning
confidence: 99%
“…Neumann et al (6) showed, using Prdx1 knockout mice, that Prdx1 expression correlated with the reactive oxygen species and the incidence of malignant disease. Moreover, our previous study using a cDNA microarray showed that one of the novel histone deacetylase (HDAC) inhibitors, FK228, induced the Prdx1 expression in the esophageal cancer cell lines and that the expression was associated with the cell toxicity of FK228 (7). The deregulation of HDACs can cause malignant diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, p21-deletion studies show that p21 is not strictly necessary for HDAC inhibitor mediated protection against oxidative stress and is only necessary for a portion of HDAC inhibitor mediated protection against DNA damage (Langley et al, 2008). Considering the number of putatively protective genes and pathways induced by HDAC inhibition [for example, p21 (Langley et al, 2008), gelsolin (Meisel et al, 2006), HSP70 (Ren et al, 2004), and peroxiredoxin-1 (Hoshino et al, 2005)], these findings are not surprising. Indeed, it is likely that the ability of HDAC inhibition to induce a number, or "cassette," of protective genes and pathways is in part responsible for the broad neuroprotection observed in vivo.…”
Section: Histone Deacetylase Inhibitors As Broadly Effective Neuropromentioning
confidence: 99%
“…The histone deacetylase inhibitors (HDACIs) were mainly thought to act by modulating the gene expression patterns, including those of genes associated with cell cycle arrest and apoptosis, by inhibiting the activity of histone deacetylases (HDACs) (5). Previous we reported that depsipeptide (FK228) and cyclic hydroxamic acid-containing peptide 31 (CHAP31) have potent antitumor effects against ESCC in vitro and in vivo (6)(7)(8) Numerous studies have demonstrated that microRNAs (miRNAs), non-coding RNAs 21-25 nucleotides in length, control gene expression by targeting mRNAs for cleavage or translational repression (9). These miRNAs are associated with important biological processes, including development, differentiation, apoptosis, and proliferation (9,10).…”
Section: Introductionmentioning
confidence: 99%